Синтез, властивостi та застосування графенових матерiалiв, отриманих з вуглецевих нанотрубок i ацетиленової сажi - Danilov, M. O.; Rusetskii, I. A.; Slobodyanyuk, I. A.; Dovbeshko, G. I.; Kolbasov, G. Ya.; Stubrov, Yu. Yu. (Publishing house "Academperiodika", 2019)
Graphene oxide and reduced graphene oxide have been chemically synthesized from multiwall carbon nanotubes. Using a proper oxidant, nanotubes can be “unzipped” longitudinally to form graphene oxide nanoribbons. Afterward, reduced graphene oxide can be obtained with the help of a reductant. Standard redox potentials of carbon are used for the selection of an oxidant and a reductant. Various physico-chemical methods are applied to verify the production of graphene-like materials. The synthesized products are used as a material for oxygen electrodes in fuel elements. The electrochemical characteristics of electrodes fabricated from graphene-based materials are found to depend on the redox ability of applied reagents. The obtained materials are shown to be promising catalyst carriers for electrodes in chemical current sources.